AnalysÄ±s of Market RÄ±sk in Stock Investment UsÄ±ng Value at RÄ±sk Method (Study on ManufacturÄ±ng CompanÄ±es in Lq-45 LÄ±sted on IndonesÄ±a Stock Exchange) - Sumaji, Yoseva Maria Pujirahayu; Hsu, Wen-Hsi Lydia; Salim, Ubud (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
Capital flows as one part of this economic growth is sourced from the capital markets namely Indonesia stock exchange. The capital markets have a function of economics because capital markets provide a facility or vehicle which brings together two interests, namely those who have excess funds and those who need funds. Before investing, investors should set a goal of investing and the magnitude of the funds invested. Any investment decisions taken have the risks borne by the investor, either investment in bonds or stocks. Stocks with known characteristics of high risk-high return, which means the stock provides an opportunity to earn high profits but also potentially high loss risk. Value at Risk (VaR) models has been extensively used not only in the banking sector but also in calculating in many sectors. The aim of this paper is to outline Value at Risk methodology by giving more emphasis on variance covariance method, historical simulation, and Monte Carlo model. The model used to investigate the applicability and usefulness of VaR in stock investment in Indonesia Manufacturing companies. Using the methodologies as described, the maximum potential loss on each stock and its portfolio of nine stocks calculated at 95% confidence level. The models were validated using back testing and Kupiec test. The research found that there are different results of VaR calculated using variance covariance, historical simulation, and Monte Carlo models. However, variance covariance model is the valid one to measure the maximum potential loss of stocks.